The GROWTH Marshal: A Dynamic Science Portal for Time-domain Astronomy. (7th February 2019) - Kasliwal, M. M.; Cannella, C.; Bagdasaryan, A.; Hung, T.; Feindt, U.; Singer, L. P.; Coughlin, M.; Fremling, C.; Walters, R.; Duev, D.; Itoh, R.; Quimby, R. M.
Abstract: We describe a dynamic science portal called the GROWTH Marshal that allows time-domain astronomers to define science programs; program filters to save sources from different discovery streams; coordinate follow-up with various robotic or classical telescopes; analyze the panchromatic follow-up data; and generate summary tables for publication. The GROWTH marshal currently serves 137 scientists, 38 science programs, and 67 telescopes. Every night, in real time, several science programs apply various customized filters to the 10 5 nightly alerts from the Zwicky Transient Facility. Here, we describe the schematic and explain the functionality of the various components of this international collaborative platform.